Report on Various Diagnostic Methods for Breast Cancer Detection in Women - A. Amir Anton Jone, T. Anita Jones Mary Puspha, Navin M George, P. Esther Jebarani, K. Martin Sagayam, Suresh Subramanian (International Journal of Advanced Science and Technology, 2020)
Breast cancer is dreadful and life threatening disease. The causative agent of breast cancer is stillunder research. Breast cancer affects one in eight women. The statistics shows that 6 percent of women in India die due to breast cancer. Breast cancer is the second important cause of death. Generallybreast cancer is a malignant tumor that begins in the cells of the breast and eventually it spreads tothe surrounding tissues. The disease can be treated if it is detected early. As stages increases, thechance of curing decreases. There are various imaging techniques that play a vital role in detectingbreast cancer. This survey is an attempt to showcase various breast cancer detection techniquesbased on image processing technique and an overview about the advantages and disadvantages ofeach technique is provided. Plenty of work has been done in this field in order to cure this deadliestdisease. The medical imaging has revolutionized the field in detecting cancer. Here by a survey ofvarious techniques that can detect cancer is presented.